The effect of sintering temperature on wear resistance of alloys produced by using hot isostatic pressing method - Tülay Yıldız; Süleyman Aba (Сверхтвердые материалы, 2019)
The present study investigated the effect of the temperature, at which a new matrix material was produced via hot isostatic pressing (HIP) method by adding certain rate of Co and Ni elements into CuSn (85/15) bronze alloy, and Co and Ni elements wear resistance of the samples produced. One of major advantages of HIP method is that heat and pressure are applied simultaneously during the sintering process. Thus, all or almost all of the pores are eliminated during the manufacturing and a denser material is obtained. Досліджено вплив температури, при якій новий матричний матеріал було отримано методом HIP (горячого ізостатичного пресування) при додаванні певного відсотка елементів Co і Ni до бронзового сплаву CuSn (85/15), а також елементів Co і Ni, на зносостійкість виготовлених зразків. Однією з головних переваг методу HIP є те, що нагрівання і тиск застосовуються одночасно у процесі спікання. Таким чином, всі або майже всі пори видаляються під час виготовлення і отримується більш щільний матеріал. Исследовано влияние температуры, при которой новый матричный материал был получен методом HIP (горячего изостатического прессования) путем добавления определенной доли элементов Co и Ni в бронзовый сплав CuSn (85/15), а также элементов Co и Ni, на износостойкость изготовленных образцов. Одним из основных преимуществ метода HIP является то, что нагревание и давление применяются одновременно во время процесса спекания. Таким образом, все или почти все поры удаляются во время изготовления, и получается более плотный материал.